Does children's dialect awareness support later reading and spelling in the standard language form?. (February 2018) - Pittas, Evdokia; Nunes, Terezinha
Highlights: Dialect awareness contributes unique variance in reading and spelling. Dialect awareness is a longitudinal predictor of reading and spelling. Measures for assessing children's awareness of their dialect in the school setting were validated.